Identification and ranking of enablers of green lean Six Sigma implementation using AHP. (2018) - Pandey, Harsha; Garg, Dixit; Luthra, Sunil
Improved environmental measures, waste reduction, cost optimisation and increased quality of products/services have now become the main objectives of the organisations. In this study, an attempt towards fulfilling the above goals has been made by proposing the concept of 'green lean Six Sigma (GLS)'. The study emphasises the implementation of GLS concept by identifying and ranking of various enablers. Five enabler dimensions and 18 enablers of GLS concept implementation have been identified through combined association of existing literature and opinions of experts' from appropriate field. Analytic hierarchy process (AHP) approach is applied for ranking of these enabler dimensions and enablers. In AHP, pair wise comparisons are all done considering the opinions of experts. Further, the obtained results are validated using sensitivity analysis.